The effectiveness of nirsevimab in reducing the burden of disease due to respiratory syncytial virus (RSV) infection over time in the Madrid region (Spain): a prospective population-based cohort study - Barbas Del Buey, José Francisco; Íñigo Martínez, Jesús; Gutiérrez Rodríguez, María Ángeles; Alonso García, Marcos; Sánchez-Gómez, Amaya; Lasheras Carbajo, María Dolores; Jiménez Bueno, Susana; Esteban Vasallo, María Dolores; López Zambrano, María Alejandra; Calvo Rey, Cristina; Sanchez Luna, Manuel; Molina Olivas, Marta; et al. (Frontiers in Public Health, 2024)
Introduction Respiratory syncytial virus (RSV) infection is one of the main causes of morbidity and mortality from lower respiratory tract infections in children under 5 years of age worldwide. Given that, the objective of this study was estimate the effectiveness of nirsevimab (a single-dose, long-acting, human recombinant monoclonal antibody against RSV) over time for the prevention of respiratory episodes treated at different levels of care. Methods A prospective and dynamic population-based cohort study was performed including infants born between April 1 and December 31, 2023, in the Madrid region who resided there during the follow-up period from October 1, 2023, to February 29, 2024. Infants were considered immunized from the day after receiving one dose (50 or 100 mg) of nirsevimab or nonimmunized individuals if they did not receive any dose. Results There were 4,100 episodes of primary care, 1,954 hospital emergencies, and 509 admissions, 82 of which required intensive care in the 33,859 participants analyzed. The adjusted effectiveness of nirsevimab in preventing hospitalization due to RSV infection was 93.6% (95% CI: 89.7 to 96.1) at 30 days and 87.6% (95% CI: 67.7 to 95.3) at 150 days. The number needed to treat to prevent one hospitalization were 314.19 (95% CI: 306.22 to 327.99) at 30 days and 24.30 (95% CI: 22.31 to 31.61) at 150 days. The adjusted effectiveness of nirsevimab in avoiding admission to an intensive care unit was 94.4% (95% CI: 87.3 to 97.5) at 30 days and 92.1% (95% CI: 64.0 to 98.3) at 90 days. The adjusted effectiveness of nirsevimab for avoiding primary care consultations and hospital emergency visits was lower. Discussion Immunization with nirsevimab is an effective measure for reducing the burden of care related to RSV at all levels of care albeit it decreases throughout follow-up. At 150 days it remained high for preventing hospital admissions. Other articles already published have also demonstrated high effectiveness although with preliminary results, short follow-up periods and wide confidence intervals. None have detected a decrease in effectiveness over time. These results can be quite useful in individual infant prevention and in the design of immunization campaigns.